Design and optimization of performance guarantees for hybrid power plants. (15th January 2022) - Ackermann, Simon; Szabo, Andrei; Bamberger, Joachim; Steinke, Florian
Abstract: This article introduces the problem of performance guarantee design for hybrid power plants (HPPs) with renewable generation. To solve it we propose a novel framework for the determination of performance guarantee levels under weather and load uncertainty. The framework is intended as a decision support tool for HPP solution providers during contract negotiations with owners, where they have to strike a balance between competitive bidding and possible contractual penalties. It is formulated as a stochastic risk-constrained optimization problem, which maximizes guarantee values subject to the risk preferences of the solution provider. HPP performance variability is included into the framework via detailed plant operation simulations. Furthermore, it allows to condition the guarantee levels on the stochastic availability of renewable resources and loads. We demonstrate the application of the framework with the design of a renewable energy output guarantee for a PV-battery storage-diesel plant. Moreover, we introduce guarantee benchmark models based on the performance ratio, least square and quantile regression and illustrate the advantages of the proposed framework in comparison to them. Performance guarantees computed with the proposed framework simplify performance risk assessment for owners and financiers in HPPs, which may lower financing costs of HPP solutions and speed up their adoption. Highlights: Novel performance guarantee design framework for hybrid power plants. 'Win-win' solution for project owner and solution provider. Maximization of guarantee values constrained by penalty risks. Islanded microgrid case study with hybrid PV-battery storage-diesel generation.